Compressive strength and microstructure of alkali-activated fly ash/slag binders at high temperature. (February 2018) - Pan, Z.; Tao, Z.; Cao, Y.F.; Wuhrer, R.; Murphy, T.
Abstract: This paper reports the results of the compressive strength and microstructure of various alkali-activated binders at elevated temperatures of 300 and 600 °C. The binders were prepared by alkali-activated low calcium fly ash/ground granulated blast-furnace slag at ratios of 100/0, 50/50, 10/90 and 0/100 wt.%. Specimens free of loading were heated to a pre-fixed temperature by keeping the furnace temperature constant until the specimens reached a steady state. Then the specimen was loaded to failure while hot. XRD, SEM and FTIR techniques were used to investigate the microstructural changes after the thermal exposure. The fly ash-based specimen shows an increase in strength at 600 °C. On the other hand, the slag-based specimen gives the worst high-temperature performance particularly at a temperature of 300 °C as compared to ordinary Portland cement binder. This contrasting behaviour of binders is due to their different binder formulation which gives rise to various phase transformations at elevated temperatures. The effects of these transformations on the compressive strength are discussed on the basis of experimental results.